Dovetail a drawer [ - Klausz, Frank; Klausz, Frank; Mastelli, Rick (A fine woodworking DVD workshop, 2003)
Frank Klausz demonstrates and explains each step in the process--cutting the stock to size, running the groove for the drawer bottom, cutting the dovetails, and gluing up and fitting the drawer.